Influência da área de reserva legal sobre a biologia da polinização de Solanum lycopersicum L. híbrido Pizzadoro (Solanaceae) - Trevizor, Ana Mayumi Hayashi (2014)
It is estimated that approximately 73 % of the world crops are pollinated by a bees. The constant alteration of habitats has led to the decline of pollinators, which may reflect limitations in the quantity and quality of the fruits and seeds grown, becoming one of the biggest problems when it comes to agricultural production. Studies with agricultural crops and their pollinators may contribute in seeking proposals that combine agriculture and conservation of forest fragments. The general objective of this work was to study aspects of Solanum lycopersicum L. hybrid Pizzadoro pollination. The specific objectives were: 1) verify if the floral morphology influences the behavior of the pollinator visits, 2) evaluate the richness of pollinating bees and pollinators at different distances from the Legal Reserve area, 3) compare the efficiency of three species of bees pollination in two treatments: spontaneous self-pollination, and pollination under natural conditions. The study was conducted on a conventional tomato cultivation in the municipality of Estiva Gerbi, Sao Paulo. Flowers were collected and observed under a stereomicroscope and scanning electron microscope. Efficiency was compared between Apis mellifera, Augochloropsis sp. and Exomalopsis sp. by Spears index. Observations and sampling were made in situ at 50, 100 and 150 meters from the Legal Reserve. It was found that the anther dehiscence is longitudinal and that the efficiency of pollination by A. mellifera (0.72) was similar to Exomalopsis sp. (0.85) and greater than Augochloropsis sp. (0.22). It is considered that the success of A. mellifera is associated with the floral morphology. Eleven species of insects, of which 7 were considered pollinators were found. Fifty eight floral visits were recorded, out of which 24 in quadrant A (50 m), 13 in B (100 m) and 21 in C (150 m), with A. mellifera dominant with 62.1% of visits, followed by Augochloropsis sp. and Oxaea flavescens both with 10.3%, Exomalopsis sp. with 6.9 %, Allograpta sp. with 5.2 % ,Bombus sp. with 3.4 % and Xylocopa sp. 1.7 %. The data indicates that the Legal Reserve played a key role in providing pollinators for tomato crops and therefore emphasizes the need for conservation and restoration of forest fragments to assist in increasing crop production.